2018
DOI: 10.1002/jsfa.8883
|View full text |Cite
|
Sign up to set email alerts
|

The influence of acid whey on the antioxidant peptides generated to reduce oxidation and improve colour stability in uncured roast beef

Abstract: The results indicated that bioactive peptides could be generated in uncured roasted beef. The <3.5 kDa peptides have strong antioxidant activity, as a result of which they function as inhibitors of lipid oxidation and colour discoloration during prolonged storage. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 30 publications
5
20
1
Order By: Relevance
“…Texture is an important sensory characteristic of muscle foods, such as pheasant and beef. Many studies [8,14,16,17,35,40,41] have indicated that the low meat pH after marinating has positive effects on the texture, which was confirmed in the present study (Table 3). In the instrumental evaluation of the texture of meat, the most commonly used parameter, interdependent with tenderness, is the value of the maximum shear force obtained by the Warner-Bratzler test.…”
Section: Resultssupporting
confidence: 88%
“…Texture is an important sensory characteristic of muscle foods, such as pheasant and beef. Many studies [8,14,16,17,35,40,41] have indicated that the low meat pH after marinating has positive effects on the texture, which was confirmed in the present study (Table 3). In the instrumental evaluation of the texture of meat, the most commonly used parameter, interdependent with tenderness, is the value of the maximum shear force obtained by the Warner-Bratzler test.…”
Section: Resultssupporting
confidence: 88%
“…The mechanism of the tenderising effect of acidic marinades involves the weakening of structures due to swelling of meat and increased conversion of collagen to gelatin at low pH during cooking (Berge et al, 2001). The acid breaks the transversal bounds of collagen, leading to the unstable structure loss of this connective tissue protein (Kumar et al, 2017;Wójciak et al, 2018). The results obtained by Ergezer and Gokce (2011) showed that the use of lactic acid for marinating turkey breast muscles decreased the value of cutting force as compared with the control.…”
Section: Resultsmentioning
confidence: 99%
“…A limited amount of research has been conducted looking at acid whey as a processing additive in meat products. According to the latest research, the use of acid whey for marinated beef improves tenderness and juiciness (Kim, 2018) and colour stability in the baked product and has an antioxidant effect (Wójciak et al, 2018); improves physicochemical properties (Ferysiuk et al, 2018) and limits oxidation of lipids in fermented sausages (Karwowska et al, 2015). Wójciak et al (2014) used acid whey with mustard seed to replace nitrites in cooked sausages, with positive effects.…”
Section: Introductionmentioning
confidence: 99%
“…Their potential activity is only activated after the release of specific amino-acid sequences, through gastrointestinal digestion or food processing (e.g., drying, curing, fermentation, or enzymatic hydrolysis). The literature data indicate processed meat products as good sources of peptides with biological activity, particularly dry-cured or fermented meats [ 13 , 14 , 15 , 16 ]. For example, the antiradical activity of protein extracts from dry-cured pork loins over a 12-month period of aging was confirmed.…”
Section: Introductionmentioning
confidence: 99%